2005
DOI: 10.1002/clc.4960280907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fluvastatin, an HMG-CoA reductase inhibitor, on serum levels of interleukin-18 and matrix metalloproteinase-9 in patients with hypercholesterolemia

Abstract: SummaryBackground: Interleukin-18 (IL-18), a novel proinflammatory marker, and matrix metalloproteinase-9 (MMP-9) represent the indices of plaque stability. It is unknown whether hydroxymethylglutaryl coenzyme A (HMG-CoA) reductase inhibitors (statins), which provide anti-inflammatory and endothelium protection effects, have the property of stabilizing plaque in patients with hypercholesterolemia.Hypothesis: The study was designed to investigate the influence of statin therapy in circulating IL-18, MMP-9, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In particular, these previous studies suggested that the stability of atherosclerotic plaques correlated with the activities of tissue MMPs [16][17][18] and that treatment with hypolipidemic drugs affected the serum level of MMPs. 19,20) To our knowledge, this is the first report showing the ability of MMPIs themselves to reduce serum levels of TG.…”
Section: Discussionmentioning
confidence: 79%
“…In particular, these previous studies suggested that the stability of atherosclerotic plaques correlated with the activities of tissue MMPs [16][17][18] and that treatment with hypolipidemic drugs affected the serum level of MMPs. 19,20) To our knowledge, this is the first report showing the ability of MMPIs themselves to reduce serum levels of TG.…”
Section: Discussionmentioning
confidence: 79%
“…In patients with hypercholesterolemia, MMP-9, IL-18 and endothelial functions were investigated in the presence or absence fluvastatin treatment. Results showed that fluvastatin, but not the placebo, reduced plasma levels of MMP-9, IL-18 and enhanced endothelial function in an independent way from its lipid lowering activity [63]. Rosuvastatin, dosedependently reduced the expression of MMP-7 levels in human monocyte-derived macrophages.…”
Section: Statins and Its Effect On A Major Scavenger Receptor On Macrmentioning
confidence: 97%
“…29,30 Some investigators report that statins increase the production of IL-18 from human peripheral blood mononuclear cells 31 whereas other content that statins reduce serum IL-18 levels. [32][33][34] The ability of HMG-CoA reductase inhibitors (statins) to modify the inflammatory process continues to attract considerable attention. The effect of statins on cytokines ranges from a reduction in circulating levels of CRP 13,35 to uncertain effects on other cytokines.…”
Section: Introductionmentioning
confidence: 99%